How Accurately Can We Measure from Video? Practical Considerations and Enhancements of the Camera Calibration Procedure. Issue 43 (December 2018) - Laureshyn, Aliaksei; Nilsson, Mikael
The accuracy of position measurements from videos depends greatly on the quality of the camera calibration model parameters. This paper investigates how such factors as camera height and the selection of calibration points affect the quality of the final calibration model. A series of controlled experiments were performed in traffic or similar-to-traffic environments, in which the accuracy of measurements from videos was compared with measurements taken with other tools. To enhance the calibration process, a multi-camera approach is suggested that utilizes the information about "common points" – points seen on several cameras but with unknown world coordinates. The performed tests showed that calibration quality can greatly benefit from this approach. The paper is addressed primarily to traffic researchers developing their own video-based tools for road user observations.